Interface modification for highly efficient organic photovoltaics - Steim, Roland; Choulis, Stelios A.; Schilinsky, Pavel; Brabec, Christoph J. (My University, 2008)
We present highly efficient inverted polymer:fullerene bulk-heterojunction solar cells by incorporation of a nanoscale organic interfacial layer between the indium tin oxide (ITO) and the metal oxide electron-conducting layer. We demonstrate that stacking of solution-processed organic and metal oxide interfacial layers gives highly charged selective low ohmic cathodes. The incorporation of a polyoxyethylene tridecyl ether interfacial layer between ITO and solution-processed titanium oxide (TiOx) raised the power conversion efficiency of inverted organic photovoltaics to 3.6%, an improvement of around 15% in their performance over comparable devices without the organic interfacial layer.
Keywords: Organic photovoltaics; Solar cells